2019
DOI: 10.15446/dyna.v86n210.72932
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin from marine microalga Isochrysis galbana: optimization of extraction methods with organic solvents

Abstract: Fucoxanthin was the carotenoid studied from the marine microalga Isochrysis galbana for its importance in preventing obesity and diabetes. In this manner, seven solvents were used to fucoxanthin extraction, highlighting methanol and ethanol with 6.282 and 4.187 mg/g, respectively. However, petroleum ether and n-hexane were the worst solvents for fucoxanthin extraction, obtaining approximately 12-folds less content. Extraction time was another relevant parameter in improve fucoxanthin extraction where 10 min wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…used seven solvents with different polarities for Isochrysis galbana fucoxanthin extraction, using an ultrasonic bath for 10 min at 25 °C. Ethanol was selected as the best solvent because of the toxicity of methanol; the best performance was achieved in 10 min with 100% ethanol, reaching 7.464 mg g −1 fucoxanthin 62 . Raguraman et al .…”
Section: Extraction Methodsmentioning
confidence: 99%
“…used seven solvents with different polarities for Isochrysis galbana fucoxanthin extraction, using an ultrasonic bath for 10 min at 25 °C. Ethanol was selected as the best solvent because of the toxicity of methanol; the best performance was achieved in 10 min with 100% ethanol, reaching 7.464 mg g −1 fucoxanthin 62 . Raguraman et al .…”
Section: Extraction Methodsmentioning
confidence: 99%
“…However, higher yield values do not necessarily bring a higher fucoxanthin content because fucoxanthin is a polar compound. It is expected that polar solvents such as methanol and acetone have higher levels of this molecule than non-polar ones such as hexane [42]. The antioxidant activity of the different extracts was assessed based on their hydroxyl radical scavenging activity.…”
Section: Solid-liquid Extraction (Sle)mentioning
confidence: 99%
“…In addition, it has the potential to replace traditional hydrothermal extraction methods due to the rapid damage it creates on the seaweed cell wall. However, it is expected to have a higher instrument cost since it uses two techniques in simultaneous [43], and a decline in power with time [42], which can affect the procedure's efficiency.…”
Section: Ultrasonic-microwave-assisted Extraction (Umae)mentioning
confidence: 99%
“…After harvesting in spring 2019, the kelp was immediately stored in a Styrofoam box without sunlight and frozen at −20 • C until further use. Elena Medina et al reported that ethanol exhibited higher efficiency at extracting fucoxanthin than chloroform, hexane, and ethyl acetate from Isochrysis galbana, a fucoxanthin-rich marine microalga [16]. Thus, the frozen kelp (2.5 kg) was cut into small pieces (around 5 cm × 10 cm) and then soaked in 50 L of ethanol for 2 days.…”
Section: Kelp Sample Preparationmentioning
confidence: 99%